The Use of Geometric Conceits in Exposition of Love in Metaphysical Poetry - Uddin, Md Eftekhar (IIUC Studies, 2009)
The language, used by Metaphysical poets is highly evocative and infused with multi-dimensional meaning. It demands comprehension and sensitivity on the part of the reader to grasp out the inner aspect of a poem. Love, being a universal feeling gets expression through the hands of different poets in different ways. The exposition of love in Metaphysical poems has shaped up in a unique way because of the juxtaposition of geometry in it. Straight line and circular line are the two components of geometry. Straight line being regarded as imperfect one as it has no limit and end is used as a vehicle to convey the imperfection of love in Metaphysical poems. On the other hand, circular line, being treated as a perfect one is used to express a harmonious union of love between human beings and also between God and human being. The article aims at exploring such conflation of love with geometry in the poetic works of John Donne, Henry Vaughn, Andrew Marvell and George Herbert, the four major Metaphysical Poets. doi: 10.3329/iiucs.v3i0.2663 IIUC STUDIES Vol. - 3, December 2006 (p 31-44)